Hygroscopicity and Ice Nucleation Properties of Dust/Salt Mixtures Originating from the Source of East Asian Dust Storms - Li, Jun; Liu, Wanyu; Castarède, Dimitri; Gu, Wenjun; Li, Linjie; Ohigashi, Takuji; Zhang, Guiqian; Tang, Mingjin; Thomson, Erik S.; Hallquist, Mattias; Wang, Sen; Kong, Xiangrui (Frontiers in Environmental Science, 2022)
Dust storms are common meteorological events that occur frequently in the late spring and early summer in arid and semi-arid areas. The resulting lofted dust and salt mixtures can impact atmospheric chemistry and climate systems through the many pathways represented by aerosol-cloud-climate interactions. In this study, dust/salt samples were collected from important sources of the East Asian dust storm, including the Badain Jaran Desert, the Tengger Desert and the Ulan Buh Desert in northwestern China. Ion chromatography (IC) measurements were performed to determine the concentrations of cations and anions. The ionic concentrations, pH and dissolvable fractions of sand samples show a positive correlation, indicating that the dissolved content is rich in alkaline ions. A positive matrix factorization (PMF) receptor model was employed to analyze the IC results, and from the PMF solutions non-obvious connections to local geography emerge. The results of hygroscopic experiments of sand samples which were measured by a vapor sorption analyzer indicate that the hygroscopicity may be related to the soluble content of samples, and the observed hygroscopic behavior can be well described by a thermodynamic model. The morphology of individual particles was chemically mapped by the synchrotron-based scanning transmission X-ray microscopy, and needle-shaped CaCO3 particles were observed to adhere to more irregular high K-containing particles. Moreover, a continuous flow diffusion chamber was used to investigate the ice nucleation abilities of typical salts, with both homogeneous freezing and deposition nucleation being observed. The results indicate that the salts primarily act as cloud condensation nuclei but can also act as ice nucleating particles at low temperatures.